2013
DOI: 10.5713/ajas.2012.12432
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Meat Quality Attributes of Indigenous Sheep and Goats from Traditional Production System in Tanzania

Abstract: The aim of the study was to compare chemical composition and quality attributes of meat between male long fat tailed sheep (n = 17) and Small East African goats (n = 17) existing in Tanzania. Animals of 1.5 to 2 yrs in age and live body weight of 22.59±0.50 kg were purchased from livestock auction markets. Animals were fasted for 18 h and slaughtered according to standard halal procedure. Left carcasses were dissected into muscles, fat and bone and the muscle and fat were mixed together and chemically analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
31
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 47 publications
(68 reference statements)
9
31
1
1
Order By: Relevance
“…Mohammad et al (2013) reported 76.2% moisture, 17.79% protein, 3.02% fat and 1.22% ash contents for sheep aged greater than 6 months and 75.12% moisture, 18.31% protein, 3.91% fat and 1.33% ash content for yearling sheep. The differences in chemical constituents of meat between studies are related to feed type and feeding regime (Guerrero et al, 2013), animals age, breed and sex differences (Shija et al, 2013).…”
Section: Chemical Composition Of Meatmentioning
confidence: 99%
“…Mohammad et al (2013) reported 76.2% moisture, 17.79% protein, 3.02% fat and 1.22% ash contents for sheep aged greater than 6 months and 75.12% moisture, 18.31% protein, 3.91% fat and 1.33% ash content for yearling sheep. The differences in chemical constituents of meat between studies are related to feed type and feeding regime (Guerrero et al, 2013), animals age, breed and sex differences (Shija et al, 2013).…”
Section: Chemical Composition Of Meatmentioning
confidence: 99%
“…As it has been observed in other breeds (Hernández-Castellano 2010;Majdoub-Mathlouthi et al 2013) between 45 min and 24 h after slaughter the pH decreased. This could be due to glycogen conversion into lactate and H+ (Shija et al 2013). An ultimate pH value greater than 5.8 is regarded as undesirable (Young et al 2004); therefore pH values after 24 h in CB and CHB can be considered acceptable.…”
Section: Ph Meat and Fat Colourmentioning
confidence: 99%
“…Fahmy et al (1992) have shown that meat characteristics such as hardness or colour parameters are related to IMF content. Shear force below 4 kg (40 N) equates an acceptable level of tenderness of the meat in Australian markets (Shija et al 2013). Hopkins et al (2006) concluded that sheep meat with shear force values less than 49 N is considered as tender.…”
Section: Journal Of Applied Animal Researchmentioning
confidence: 99%
“…For all crops, livestock/poultry, fisheries/aquaculture categories used for this study, proximate compositions were acquired from international food composition tables or other published compendia and primary sources .…”
Section: Methodsmentioning
confidence: 99%